Cytotoxic analogs of luteinizing hormone-releasing hormone containing doxorubicin or 2-pyrrolinodoxorubicin, a derivative 500-1000 times more potent. - Nagy, A (1996)
Doxorubicin (DOX) and its daunosamine-modified derivative, 2-pyrrolino-DOX, which is 500-1000 times more active than DOX, were incorporated into agonistic and antagonistic analogs of luteinizing hormone-releasing hormone (LH-RH). The conjugation of DOX with LH-RH analogs was performed by using N-(9-fluorenylmethoxycarbonyl)-DOX-14-O-hemiglutarate, a dicarboxylic acid ester derivative of DOX. Coupling this derivative covalently to the epsilon-amino group of the D-Lys side chain of agonist [D-Lys6]LH-RH or antagonistic analog AC-D-Nal(2)-D-Phe(4Cl)-D-Pal(3)-Ser-Tyr-D-Lys-Leu-Arg-Pro-D-Ala-NH 2 [where Nal(2) = 3-(2-naphthyl)alanine, Pal(3) = 3-(3-pyridyl)alanine, and Phe(4CI) = 4-chlorophenylalanine] was followed by the removal of the 9-fluorenylmethoxycarbonyl protective group to yield cytotoxic derivatives of LH-RH analogs containing DOX. From these DOX containing LH-RH hybrids, intensely potent analogs with daunosamine-modified derivatives of DOX can be readily formed. Thus, cytotoxic LH-RH agonist containing DOX (AN-152) can be converted in a 66% yield by a reaction with a 30-fold excess of 4-iodobutyraldehyde in N,N-dimethylformamide into a derivative having 2-pyrrolino-DOX (AN-207). Hybrid molecules AN-152 and AN-207 fully preserve the cytotoxic activity of their radicals, DOX or 2-pyrrolino-DOX, respectively, in vitro, and also retain the high binding affinity of the peptide hormone portion of the conjugates to rat pituitary receptors for LH-RH. These highly potent cytotoxic analogs of LH-RH were designed as targeted anti-cancer agents for the treatment of various tumors that possess receptors for the carrier peptide. Initial in vivo studies show that the hybrid molecules are much less toxic than the respective cytotoxic radicals incorporated and significantly more active in inhibiting tumor growth.